Which isn’t known by addition (Journal of the College of Basic Education, 2022)
In the Name of Allah, the Most Gracious, the Most MercifulPraise be to God and prayers and peace be upon the best creation of God Muhammad and his family and companions.After that:The addition in Arabic is a large subject, so I chose a part of it (Which isn’t known by addition). And the addition in the language means inclination and attribution, so whenever I incline to something and attribute to it I may add.As for the idiomatic meaning, it is an attribution of a noun to another one, demoting the second one from the first one its nunnation, or what replaces its nunnation, accordingly, it is required to bare the adjunct from the nunnation (Ghulam Zaid), and from the noon (N) like (Ghulami Zaid), and that because of the noon (N) of the two (Al-Muthana) and the total apart substitute the singular nunnation.One of the characteristics of the addition is that it makes the two names that are added the one thing that doesn’t separate one from the other and neither of them has any meaning except in addition to its spouse.In the addition, there is no choice but put the second name completely in the ablative case and this type of ablative considers as a partner to the ablative of the letter and comparable to it.As for the types of addition, they are pure addition and impure addition. The pure one which is also called the abstract, benefits a definition or specialization, as for the definition like (Dar Amro- house of Amro). As for specialization, it is called "Ghulam man". It is also called the pure addition, i.e.: the meaning is in accordance with the word.This edition includes the addition of the non-descriptive like (Ghulam Zaid), and the addition of the description to the non-working like (Dhareb Zaid Ams - beating Zaid yesterday) (the adjunct, although it was an adjective the governed it is not working to it; because the participle (noun of the subject) does not work if it’s in the sense of the past). But though we find that there are some words added and remained opaque and did not recognize.These words are called (Which isn’t known by addition):(A) Participle and past participle (noun of subject and noun of the object) and the resemble adjective in the case of adding them to their workings, which are indicative of the adverb and the reception, they remain indefinite.(B) The adverb and the joined of discrimination and the noun of the negative (Not-La) that added to the definite.(C) Nouns were added to the definites and did not recognize such as: (Hasbok-, Hudak, and Naheek, Charaka, Charaka, and mithlaka -like you).Finally, I ask Allah the Highest, the Protector, and the best supporter.